Genetic Transformation in Nicotiana tabacum Using Pollen as a Vector - Wantana Tangpremsri (Agriculture and Natural Resources, 1994)
The pollen grains of Nicotiana tabacum were grown on artificial media containing 10.25% sucrose and0.001% boric acid and used in the pollen transformation experiment. The experiment was undertaken to investigate the potential use of pergerminated pollen as a vector for genetic transformation by using the kanamycin resistant gene (plasmid pLGV neo 1103). Eighteen different electroporation treatments were tested for the ability to encourage the uptake of the plasmid pLGV neo 1103 gene into the pergerminated pollen grains. The vest electroporation treatment was 250 V/cm, 250 µF and 2 or 4 pulses which produced 3.8% potentially transformed seeding. Kanamycin resistance was expressed in seeding callus and regenerated plants.